In vitro antibacterial efficacy of a novel chicken-derived Bacillus subtilis GX15 strain and its protective mechanisms in mice challenged by Salmonella enterica serovar typhymurium - Huili Bai; Yuying Liao; Jingshan Lu; Zhe Pei; Yangyan Yin; Chunxia Ma; Zhongwei Chen; Changting Li; Jun Li; Yu Gong; Ling Teng; Leping Wang; et al. (BMC Microbiology)
Abstract Background The escalating issue of bacterial resistance, coupled with stringent restrictions on antibiotic use in many countries, has prompted the search for alternative strategies to combat bacterial infections. Probiotics, such as Bacillus subtilis (B. subtilis), have been widely recognized for their ability to inhibit pathogenic bacteria proliferation and protect hosts from infection-related damage. Results In this study, a novel strain of B. subtilis, designated GX15, was isolated from the intestine of a healthy chicken. We systematically evaluated its in vitro antimicrobial activity and protective effects against Salmonella Typhimurium SM022 (S. Typhimurium SM022) infection in mice. GX15 exhibited broad-spectrum antibacterial activity, effectively inhibited the growth of both Gram-positive and Gram-negative bacteria, including S. Typhimurium SM022, Escherichia coli, and Staphylococcus aureus. In a murine model, S. Typhimurium SM022 infection induced clinical symptoms such as diarrhea, anorexia, and fur ruffling in C57BL/6 mice. Oral administration of GX15 at 10⁸ CFU/mL significantly attenuated these effects, reducing the elevation of immune organ indices, limiting bacterial translocation to peripheral tissues, and alleviating histopathological damage to the liver and intestinal tissues. Notably, GX15 did not alter antioxidant indices or immunoglobulin levels. However, it markedly modulated the expression of cytokines including GM-CSF, IL-6, TLR2, IL-10, and TGF-β in the small intestine, suggesting an immunoregulatory mechanism of action. Conclusion B. subtilis GX15 exhibits potent probiotic activity and represents a promising prophylactic candidate against S. Typhimurium infections. These findings provide valuable insights into the potential use of GX15 as an alternative strategy for the prevention and control of salmonellosis.